Testing the lexical hypothesis are socially important traits more densely reflected in English lexicon? [article]. - Wood, Dustin
Using a set of 498 English words identified by Saucier (1997) as common person descriptor adjectives or trait terms, I tested 3 instantiations of the lexical hypothesis, which posit that more socially important person descriptors show greater density in the lexicon. Specifically, I explored whether trait terms that have greater rational impact (i.e., more greatly influence how others respond to a person) have more synonyms, are more frequently used and are more strongly correlated with other trait terms and other terms. I found a little evidence to suggest that trait terms rated as having greater relational impact where more frequently used or had more synonyms. However, these terms correlated more strongly with other trait terms in the set. Conversely, a trait term?s loadings on structural factors (e.g., the big five, hexaco) were extremely good predictors of thee term?s relational impact. The findings suggest that the lexical hypothesis may not be strongly supported in some ways it is commonly understood but is supported in the manner most important to investigations of traits structure. Specifically, trait terms with greater relational impact tend to more strongly correlate with other terms in lexical sets and thus have a greater role in driving the location of factors in analysis of trait structure. Implications of understanding the meaning of lexical factors such as the big five are discussed. - - (from the authors)
Keywords: Lexical hypothesis-Periodicals.; Trait structure-Periodicals.; Social desirability-Periodicals.; Personality traits-Periodicals.